Potential Repair of Escherichia coli DNA following Exposure to UV Radiation from Both Medium- and Low-Pressure UV Sources Used in Drinking Water Treatment - Zimmer, J. L. (American Society for Microbiology, 2002)
The increased use of UV radiation as a drinking water treatment technology has instigated studies of the repair potential of microorganisms following treatment. This study challenged the repair potential of an optimally grown nonpathogenic laboratory strain of Escherichia coli after UV radiation from low- and medium-pressure lamps. Samples were irradiated with doses of 5, 8, and 10 mJ/cm(2) from a low-pressure lamp and 3, 5, 8, and 10 mJ/cm(2) from a medium-pressure UV lamp housed in a bench-scale collimated beam apparatus. Following irradiation, samples were incubated at 37°C under photoreactivating light or in the dark. Sample aliquots were analyzed for up to 4 h following incubation using a standard plate count. Results of this study showed that E. coli underwent photorepair following exposure to the low-pressure UV source, but no repair was detectable following exposure to the medium-pressure UV source at the initial doses examined. Minimal repair was eventually observed upon medium-pressure UV lamp exposure when doses were lowered to 3 mJ/cm(2). This study clearly indicates differences in repair potential under laboratory conditions between irradiation from low-pressure and medium-pressure UV sources of the type used in water treatment.